2006
DOI: 10.4049/jimmunol.177.7.4907
|View full text |Cite
|
Sign up to set email alerts
|

An Unconventional Antigen Translated by a Novel Internal Ribosome Entry Site Elicits Antitumor Humoral Immune Reactions

Abstract: Self-tumor Ags that elicit antitumor immune responses in responses to IFN-α stimulation remain poorly defined. We screened a human testis cDNA library with sera from three polycythemia vera patients who responded to IFN-α and identified a novel Ag, MPD6. MPD6 belongs to the group of cryptic Ags without conventional genomic structure and is encoded by a cryptic open reading frame located in the 3′-untranslated region of myotrophin mRNA. MPD6 elicits IgG Ab responses in a subset of polycythemia vera patients, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…45,46 In this regard, the recently identified PV-associated tumor antigens may represent targets for immune effectors. 47,48 The time interval between hematologic and MRs observed in the present study could suggest that direct cytotoxic and antiproliferative properties of IFN were responsible for the rapid hematologic response (within 3 months in ϳ 90% of the patients), whereas immune-mediated mechanisms could be involved in MR, achieved later.…”
Section: Discussionmentioning
confidence: 57%
“…45,46 In this regard, the recently identified PV-associated tumor antigens may represent targets for immune effectors. 47,48 The time interval between hematologic and MRs observed in the present study could suggest that direct cytotoxic and antiproliferative properties of IFN were responsible for the rapid hematologic response (within 3 months in ϳ 90% of the patients), whereas immune-mediated mechanisms could be involved in MR, achieved later.…”
Section: Discussionmentioning
confidence: 57%
“…To our knowledge, this is a part of the first such a study in BCR-ABL negative MPD [1,6]. The analyses showed that these novel tumor antigens are not identical to any hematologic malignancy antigens identified previously with SEREX [17] or other approaches [22,42].…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant progress, the self-antigen targets that may mediate immune reactions contributing to beneficial responses to therapies in patients with myeloproliferative diseases (MPD) remained poorly defined before our recent report in characterization of a new unconventional tumor antigen MPD6 [6]. Recent reports showed that mRNA of polycythemia rubra vera-1 (PRV-1) is overexpressed in mature peripheral blood granulocytes from patients with PV [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of novel antigens by PV cells that are capable of eliciting a potent humoral immune response has been associated with the achievement of molecular remissions. 42,43 IFN␣ therapy has been reported to up-regulate a putative tumor antigen termed MPD6, which is encoded by a cryptic open reading frame located in the 3Ј-untranslated region of myotrophin mRNA by a novel internal ribosome entry site upstream of the MPD6 reading frame. 43 Furthermore, type 1 IFNs also enhance antibody responses to soluble antigens and promote immunoglobulin class switching.…”
Section: The Effects Of Ifn␣ On Immune Modulatory Cellsmentioning
confidence: 99%